Varieties of winter wheat in eastern Colorado require different n recommendations for achieving grain yield and protein content - Kluth, Danica, author; Johnson, Jerry J., advisor; Ippolito, James A., advisor; Peairs, Frank B., committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: cultivar; sulfur; Colorado; winter wheat; nitrogen